Personal Listening Devices in Australia: Patterns of Use and Levels of Risk - Gilliver, Megan; Nguyen, Jenny; Beach, Elizabeth F.; Barr, Caitlin (Seminars in Hearing, 2017)
Personal listening devices (PLDs) have the potential to increase the risk of noise-induced hearing loss (NIHL) for users. The present study aimed to investigate the nature and extent of the risk posed, by describing the user profile of a PLD population, identifying listening habits of that population, and examining whether PLD risk status is associated with hearing damage. A sample of 4,185 Australian PLD users completed an online survey about listening behaviors and hearing health. Listeners were characterized as low, high, or very high-risk based on daily noise dose estimates calculated from self-reported listening volume and durations. Listening patterns and hearing difficulties were examined in relation to risk status. Results indicated differences in listening volumes and durations with respect to age, with higher listening volumes reported for environments with greater background noise. Fifteen percent of participants' usage was classified as posing a potential risk to hearing, with a significantly greater proportion of younger people in higher-risk categories. Forty-one percent of participants reported feeling they have a hearing loss, with ∼20% reporting difficulties with speech in noise. For 18- to 35-year-olds, higher-risk status was associated with a greater proportion of self-reported hearing difficulties, including perceived poorer speech perception. These results have implications for hearing health promotion activities and suggest that messages should focus on either volume levels or durations depending on the particular activity in which the PLD is used. In addition, the results underline the importance of placing PLD exposure in the context of individuals' wider noise exposure. Although PLD use alone is not placing the majority of users at risk, it may be increasing the likelihood that individuals' cumulative noise exposure will exceed safe levels.
Keywords: Personal listening devices; hearing health; noise-induced hearing loss; leisure noise exposure